MicroRNA: A Bridge from H. pylori Infection to Gastritis and Gastric Cancer Development - Zabaleta, Jovanny (Frontiers in Genetics, 2012)
Helicobacter pylori (H. pylori) infection is a recognized risk factor for gastric cancer. The disease is one of the most common in the world and explains for a significant number of cancer cases and cancer-associated deaths worldwide. H. pylori infection induces huge array of responses at the gastric epithelial cells and the immune system, inducing both pro- and anti-inflammatory molecules that are intended to either perpetuate or control the infection. Despite the strong immune response, the infection is not cleared and can persist mostly without causing major significant discomfort in the human host. Among the mediators induced in response to the infection, microRNA (miRNA) have the potential to play a major impact on the outcome of the bacteria-host interaction. These miRNA are small 18–24 nucleotide long nucleotide molecules that can interact with mRNA molecules and block their translation into proteins or induce their degradation. Many efforts have been put into the generation of miRNA profiles and their role in gastric cancer. This has led to the identification of miRNA associated with promoting the inflammatory response initiated by the H. pylori infection, increasing the malignant progression of the gastric epithelium, and enhancing the invasiveness and migratory capacity of cancer cells. However, at the same time, several miRNA have been associated with events that are totally opposite, leading to reduced inflammation, inhibition of malignancy and increased apoptosis of transformed cells. In summary, as it is in many other examples, the role played by miRNA in gastric cancer is the results of a delicate balance between pro- and anti-cancer miRNA, and this balance is modified by the interaction of many players, many of which are still waiting to be discovered.